Ki Hajar Dewantara's Educational Philosophy as the Foundation of Education in the Digital Era - Bima Wisnu Gunawan; Wasilatur Rohmah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Considering the ever-evolving digital era, this study seeks to examine the application and relevance of Ki Hajar Dewantara’s educational philosophy. Ki Hajar Dewantara, a highly influential figure in Indonesian education, held a rich and comprehensive pedagogical vision. However, it is necessary to evaluate how these conventional methods can be applied amidst the substantial challenges and transformations brought about by digital technology in the field of education. This article explores the educational principles of Ki Hajar Dewantara, including